KONTRIBUSI INFORMASI TERHADAP MINAT SISWA SMK N 3 KOTA SUNGAI PENUH UNTUK MELANJUTKAN PENDIDIKAN KE JURUSAN ILMU KESEJAHTERAAN KELUARGA FPP-UNP - Gusmira, Gusmira; Ernawati, Ernawati; Novrita, Sri Zulfia (Faculty of Tourism and Hospitality - Universitas Negeri Padang, 2017)
This study aims to (1) find out information about IKK Department among students of SMK N 3 Kota Sungai Penuh, (2) find out students interest of SMK N 3 Kota Sungai Penuh continuing education to IKK Department and (3) to see the contribution of information for student interest SMKN 3 Sungai full when they continue they education to the Department of IKK FPP-UNP. This research was descriptive kuantitatif. The population in this study were the students of XII grade in SMK N 3 Kota Sungai Penuh Department of Culinary and Department of Clothing which amounted to 124 students with a sample of 55 students. The sample is taken by simple random sampling. Data collection used questionnaires arranged in Likert scale that has been tested for its validity and reliability. The study has analyzed by multiple regression analysis. The results showed that: 1) Information about IKK FPP-UNP was categorized as high as 56.36%. 2) The students interest to continue their education to IKK FPP-UNP was categorized as high as 43.63%. 3) contribution of information for student interest SMK N 3 Kota Sungai Penuh to continue they education to Department of IKK FPP-UNP amount to 41,5%, while rest was determined by other variable that not examined in this research.Keywords: Information, Interests, SMK N 3 Kota Sungai Penuh.